PENGARUH SUHU PENGERINGAN TERHADAP KANDUNGAN KOMPONEN BIOAKTIF DAN KARAKTERISTIK SENSORIS TEH WHITE PEONY - Ulandari, Dewa Ayu Tri; Nocianitri, Komang Ayu; Arihantana, Ni Made Indri Hapsari (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 1 (2019): Jurnal ITEPA, 2019)
This study aims to determine the effect of drying temperature on the bioactive component contents of white peony tea and to know the proper drying temperature in white peony tea to produce the highest bioactive component contents and the best sensory characteristics. The experimental design used was Completely Randomized Design with a drying temperature as the treatment consisting of five levels: 60 o C, 70 o C, 80 o C, 90 o C, and 100 o C. The treatment was repeated 3 times to obtain 15 experiment units . The data obtained were analyzed by variance and if the treatment had an effect on the observed variable then continued with The Duncan Multiple Range Test . The results showed that the 90 o C drying temperature treatment produced white peony tea with the highest bioactive component contents and the best sensory characteristics with water content 4,06 % (wet basis), yield 52,54% , total phenolic 211,01 mg GAE/g tea, flavonoid 10,90 mg CE/g tea, catechin 3,55 mg/g tea, antioxidant activity 50,20%, brew color yellow and liked, astringent taste and usual, aroma liked and overall acceptance rather liked.